BETULINIC ACID WAS MORE CYTOTOXIC TOWARDS THE HUMAN BREAST CANCER CELL LINE MDA-MB-231 THAN THE HUMAN PROMYELOCYTIC LEUKAEMIA CELL LINE HL-60 - LATIFAH SAIFUL YAZAN; FAUJAN HAJI AHMAD; OOI CHOONG LI; RAHA ABDUL RAHIM; HISYAM ABDUL HAMID; LEE PEI SZE (Universiti Sains Malaysia, 2009)
Betulinic acid (BA) is a pentacyclic triterpene found in several botanical sources that has been shown to cause apoptosis in a number of cell lines. This study was undertaken to determine the in vitro cytotoxic properties of BA towards the human mammary carcinoma cell line MDA-MB-231 and the human promyelocytic leukaemia cell line HL-60 and the mode of the induced cell death. The cytotoxicity and mode of cell death of BA were determined using the MTT assay and DNAfragmentation analysis, respectively. In our study, the compound was found to be cytotoxic to MDA-MB-231 and HL-60 cells with IC50 values of 58 μg/mL and 134 μg/mL, respectively. Cells treated with high concentrations of BA exhibited features characteristic of apoptosis such as blebbing, shrinking and a number of small cytoplasm body masses when viewed under an inverted light microscope after 24 h. The incidence of apoptosis in MDA-MB-231 was further confirmed bythe DNA fragmentation analysis, with the formation of DNA fragments of oligonucleosomal size (180-200 base pairs), giving a ladder-like pattern on agarose gel electrophoresis. BA was more cytotoxic towards MDA-MB-231 than HL-60 cells, and induced apoptosis in MDA-MB-231 cells.